Distribution frequencies of KIR genes among the Korean, Manchu and Han ethnic groups in Jilin Province - HAN Yu; YANG Fan; LIU Lingling; NIE Tingting; YANG Xu; JIAO Lixin (Zhongguo shuxue zazhi)
Objective To provide foundational data for exploring the association between KIR genes and diseases by analyzing the frequency and polymorphism of killer-cell immunoglobulin-like receptor (KIR) genes in Han, Manchu and Korean populations in Jilin Province. Methods KIR gene typing was performed on 129 Manchu, 198 Korean and 201 Han individuals from Jilin using the polymerase chain reaction-sequence specific primers (PCR-SSP) technique. Results KIR3DL2, KIR3DL3, KIR3DP1 and KIR2DL4 were detected in all subjects. KIR2DL1, KIR2DL3, KIR2DS4, KIR3DL1 and KIR2DP1 genes had high detection frequencies, ranging from 93% to 98% across the three ethnic groups. In contrast, the detection rates of KIR2DL2, KIR2DL5, KIR3DS1, KIR2DS1, KIR2DS2, KIR2DS3 and KIR2DS5 were lower, ranging from 13% to 45%. Notably, the detection frequencies of KIR2DL5 (17.83%) and KIR2DS1 (17.83%) in the Manchu population were significantly lower than those in the Korean (42.93%, 47.47%) and Han (33.83%, 33.33%) populations in Jilin. The detection frequencies of KIR2DL5 (42.93%) and KIR2DS1 (47.47%) were significantly higher in the Korean population compared to the Han (33.83%, 33.33%) and Manchu (17.83%, 17.83%) population. The frequency of the KIRAA haplotype in the Han population was the highest among the three ethnic groups in Jilin at 61.19%, significantly higher than that in the Korean population (42.93%). Differences between the three groups were statistically significant (P<0.05), and remained significant after Bonferroni correction (Pc<0.05). Conclusion The distribution of KIR genes in the Korean, Manchu and Han population in Jilin reflects the polymorphism of KIR genes in the Chinese population and also showcases unique ethnic genetic and regional characteristics.